Smart Academic Chatbot for Student Information Services Based on Transformer-Fine Tuning - Muhammad Nazwan; Ananda Hilmy; Azua Ramadhan; Fernandi Lucky Putra; Natasya Nur Hadi; I Gusti Bagus Agung Dharmaya; Mhd Adi Setiawan Aritonang; Deosa Putra Caniago (Aptikom Kepri, 2026)
This research developed a Transformer-based Smart Academic Chatbot using the fine-tuning method to generate more accurate responses tailored to students' needs. The development process follows the Waterfall model, starting from the collection of academic question-answer data, pre-processing, architecture design, to implementation and testing. The evaluation results show that the chatbot is able to provide relevant answers with a good level of accuracy, as well as improve the ease of access to academic information. This system has the potential to be a smart solution in supporting the digital transformation of campus academic services.